El sistema agroalimentario de la ciudad de Puebla después de la pandemia de COVID-19 - Varillas Lima, Juan Carlos (2024)
This research analyzes the effects of COVID-19 pandemic in the agriculture-food system of Puebla, Mexico; considering production, supply-distribution and consumption of food subsystems. To study the contingency consequences, the case of “Central de Abastos de la Ciudad de Puebla” was selected as a wholesale market where the main players (producers, wholesalers and consumers) coexist. Qualitative method was applied representing the results of two surveys in this market, one of them in 2018, before pandemic, and the other in 2022, after health crisis. For the survey information and available statistics about food production, trade and food prices, some aspects were discovered: the negative effects of pandemic were produced by structural points of food system in neoliberal period and the resilience of agriculture system supported by rural producers city of Puebla suburbs who produced enough volume of food to supply the wholesale. This is a research focus to create a food public policy to attend the structural problems and also to mitigate the contingency effects like pandemic occurred between 2019 and 2022.